Gold nanoparticles deposited on glass: physicochemical characterization and cytocompatibility - Reznickova, Alena; Novotna, Zdenka; Kasalkova, Nikola Slepickova; Svorcik, Vaclav (Nanoscale research letters, 2013)
Properties of gold films sputtered under different conditions onto borosilicate glass substrate were studied. Mean thickness of sputtered gold film was measured by gravimetry, and film contact angle was determined by goniometry. Surface morphology was examined by atomic force microscopy, and electrical sheet resistance was determined by two-point technique. The samples were seeded with rat vascular smooth muscle cells, and their adhesion and proliferation were studied. Gold depositions lead to dramatical changes in the surface morphology and roughness in comparison to pristine substrate. For sputtered gold structures, the rapid decline of the sheet resistance appears on structures deposited for the times above 100 s. The thickness of deposited gold nanoparticles/layer is an increasing function of sputtering time and current. AFM images prove the creation of separated gold islands in the initial deposition phase and a continuous gold coverage for longer deposition times. Gold deposition has a positive effect on the proliferation of vascular smooth muscle cells. Largest number of cells was observed on sample sputtered with gold for 20 s and at the discharge current of 40 mA. This sample exhibits lowest contact angle, low relative roughness, and only mild increase of electrical conductivity.